Speech Recognition with Amplitude and Frequency Modulations - Zeng, Fan-Gang; Nie, Kaibao; Stickney, Ginger S.; Kong, Ying-Yee; Vongphoe, Michael; Bhargave, Ashish; Wei, Chaogang; Cao, Keli; Merzenich, Michael M. (Proceedings of the National Academy of Sciences - PNAS, 2005)
Amplitude modulation (AM) and frequency modulation (FM) are commonly used in communication, but their relative contributions to speech recognition have not been fully explored. To bridge this gap, we derived slowly varying AM and FM from speech sounds and conducted listening tests using stimuli with different modulations in normal-hearing and cochlear-implant subjects. We found that although AM from a limited number of spectral bands may be sufficient for speech recognition in quiet, FM significantly enhances speech recognition in noise, as well as speaker and tone recognition. Additional speech reception threshold measures revealed that FM is particularly critical for speech recognition with a competing voice and is independent of spectral resolution and similarity. These results suggest that AM and FM provide independent yet complementary contributions to support robust speech recognition under realistic listening situations. Encoding FM may improve auditory scene analysis, cochlear-implant, and audiocoding performance.